Prenatal Hyperhomocysteinemia Leads to Synaptic Dysfunction and Structural Alterations in the CA1 Hippocampus of Rats - Tatyana Y. Postnikova; Alexandra V. Griflyuk; Natalia L. Tumanova; Nadezhda M. Dubrovskaya; Anastasia V. Mikhel; Dmitriy S. Vasilev; Aleksey V. Zaitsev (Biomolecules, 2025)
Prenatal hyperhomocysteinemia (HCY) is associated with neurodevelopmental deficits, yet its long-term impact on hippocampal synaptic function remains poorly understood. This study examines the effects of moderate maternal HCY on excitatory synaptic transmission in the CA1 region of the dorsal hippocampus in rat offspring at juvenile (P21) and adult (P90) stages. Using field postsynaptic potential (fPSP) recordings, electron microscopy, and Western blot analysis, we observed a significant age-dependent decline in the efficiency of excitatory synaptic transmission in HCY-exposed rats. Electron microscopy revealed structural alterations, including synaptic vesicle agglutination in the stratum radiatum, suggesting impaired neurotransmitter release. Additionally, a significant reduction in pyramidal neuron density was observed in the CA1 region, although seizure susceptibility remained unchanged. Western blot analysis showed altered expression of Synapsin I, indicating presynaptic dysfunction. These findings suggest that moderate prenatal HCY leads to persistent deficits in synaptic transmission and structural integrity, potentially contributing to cognitive impairments in adulthood. Our results highlight the importance of maternal homocysteine levels in shaping hippocampal function and could offer insights into neurodevelopmental disorders associated with metabolic disturbances.